A “Convenient Euthanasia”: O papel da eutanásia na obra de H. G. Wells - Miguel Oliveira, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
In recent decades, assisted dying has become one of the most divisive issues in contemporary society. It continues to divide expert opinion and remains an issue for which no social consensus has yet emerged. However, this debate has roots in Victorian society in the late 19th century, where many arguments used today, both for and against assisted dying, were already anticipated. After World War II, the discussion shifted to the fields of bioethics, law, and medicine. Nevertheless, its genesis was marked by the eugenic theories and social Darwinism prevalent in the late Victorian and early Edwardian periods. The prevailing ideas of the time had a profound influence on both society and the literary works of prominent authors. In speculative fiction, futuristic and alternative universes already incorporated assisted dying as an established practice. This study analyses the impact of the euthanasia debate in the novel When The Sleeper Wakes and the novella “A Story of the Days to Come”, both published by H. G. Wells in 1899.